Frontiers in Algorithmics 4th International Workshop, FAW 2010, Wuhan, China, August 11-13, 2010. Proceedings - Lee, Der-Tsai.; Chen, Danny Z.; Ying, Shi. (Lecture Notes in Computer Science,, 2010)
This book constitutes the refereed proceedings of the 4th International Frontiers of Algorithmics Workshop, FAW 2010, held in Wuhan, China, in August 2010. The 28 revised full papers presented together with the abstracts of 3 invited talks were carefully reviewed and selected from 57 submissions. The Workshop will provide a focused forum on current trends of research on algorithms, discrete structures, and their applications, and will bring together international experts at the research frontiers in these areas to exchange ideas and to present significant new results. The mission of the Workshop is to stimulate the various fields for which algorithmics can become a crucial enabler, and to strengthen the ties between the Eastern and Western research communities of algorithmics and applications.